Triple Threat: A Case Report of Phenytoin, Lamotrigine and Oxcarbazepine Induced Toxic Epidermal Necrolysis - Chavakala, Bhaskar Rao; Chintha, Likhitha; Gurugari, Yeshwanth; Cheppalli, Poojitha Reddy; Dornadula, Giri Raja Sekhar; Meriga, Pramod Kumar; Mallela, Sireesha (Indian Journal of Pharmacy Practice)
Rationale: Toxic Epidermal Necrolysis (TEN) is a potentially life-threatening dermatologic disorder that can be triggered by medications, infections, vaccines, or idiopathic causes. According to reports from the EuroSCAR study, certain drugs such as Lamotrigine, Carbamazepine, Phenytoin, Nevirapine, Sulfonamides, and Allopurinol pose a high risk of causing TEN. Patient Concerns: A 55-year-old male presented with a maculopapular rash all over his body persisting from last six days. After a thorough review of the patient’s medical and medication history, it was a suspected reaction induced by Lamotrigine, Oxcarbazepine, and Phenytoin, which were prescribed to manage his seizure episodes. Diagnosis: The patient was diagnosed with Toxic Epidermal Necrolysis triggered by Lamotrigine, Oxcarbazepine, and Phenytoin. Intervention: Treatment included discontinuation of all offending drugs and administration of various medications, including Inj. Dexamethasone, Inj. Taxim 1 g, T. Cetirizine 10 mg, T. BC/Ca/Vit C/Cap A&D, Fubiset cream for erosions, Dologel oral paste, Candid mouth paint, Kenocort oral paste for oral erosions, saline soaking for haemorrhagic crusting over lips, Povidone iodine mouth gargling, kenocort paste for scrotal erosion, Emollient, Inj. H. Actrapid, and T. Amlodipine. Outcomes: The patient responded well to treatment, with resolution of the rashes after five days of treatment. He was discharged from the hospital with instructions to continue T. Prednisone 5 mg OD, T. Cetrizine 10 mg OD, Dologel oral paste, Kenocort oral paste, and Candid mouth paint. Conclusion: This case highlights the critical importance of vigilant medication management and early intervention in suspected drug-induced cutaneous adverse reactions. Lesson: Patients using suspected drugs should be monitored closely. If they encounter any suspected adverse reactions, these drugs should be dechallenged immediately for better outcomes. This situation emphasizes the importance of proactive education for both patients and healthcare providers regarding potential adverse drug reactions, especially in high-risk populations, to prevent similar incidents from occurring in the future.
Keywords: Toxic Epidermal Necrolysis; Anti convulsants; Adverse drug reaction; Maculopapular rash; Case report